Dll1 haploinsufficiency causes brain abnormalities with functional relevance - Arzate, Dulce-María; Valencia, Concepción; Dimas, Marco-Antonio; Antonio-Cabrera, Edwards; Domínguez-Salazar, Emilio; Guerrero-Flores, Gilda; Gutiérrez-Mariscal, Mariana; Covarrubias, Luis (Frontiers in Neuroscience, 2022)
The Notch pathway is fundamental for the generation of neurons during development. We previously reported that adult mice heterozygous for the gene encoding the Delta-like ligand 1 for Notch (Dll1+/lacZ) have a reduced neuronal density in the substantia nigra pars compacta. The aim of the present work was to evaluate whether this alteration extends to other brain structures and the behavioral consequence of affected subjects. Dll1+/lacZ mice have a reduced brain weight and size in comparison to WT litter-mates (i.e., mild microcephaly), a phenotype detected early after birth. Interestingly, enlarged ventricles (i.e., hydrocephalus) was a common characteristic of brains of Dll1 haploinsufficient mice since early ages. At the cell level, several brain areas (e.g., cortex, hippocampus, substantia nigra, striatum) of Dll1+/lacZ mice as compared with WT mice showed a reduced number of neurons, with significant differences detected in the cortex and the dentate gyrus. Also a reduced number of astrocytes were found in some brain structures of Dll1+/lacZ mice, but in the cortex a significant increase was apparent. Furthermore, the number of adult neural stem cells was particularly reduced in the dentate gyrus of Dll1+/lacZ mice but not in the subventricular zone. Alterations in the myelination developmental pattern were evident in Dll1+/lacZ mice and consistent with premature oligodendrocyte differentiation. After applying a set of behavioral tests, mild neurological deficits were detected that result in alterations in motor behaviors, and a deficit in object categorization was evident. Our observations suggest that Dll1 haploinsufficiency limits Notch signaling to levels that cause brain abnormalities with functional relevance.